Precipitation of de novo atrial fibrillation during Shockwave Intravascular Lithotripsy® after pacing capture during the treatment of proximal right coronary artery disease: a case report. Issue 4 (27th September 2019) - Curtis, Elizabeth; Khan, Ali; El-Jack, Seif; Glenie, Tim
Abstract: Background: Shockwave Intravascular Lithotripsy ® has been recently translated to the treatment of coronary artery disease with a long history of use for ureteric stones where it has been observed to have caused cardiac arrhythmias. The risk of arrhythmia with the use of this method in coronary artery disease is currently unknown. Case summary: A 72-year-old man undergoing planned percutaneous intervention to a heavily calcified proximal right coronary artery (RCA) lesion using S-IVL developed pacing capture from the device and subsequently new atrial fibrillation (AF) during the procedure. The technique resulted in successful treatment of the coronary lesion and he spontaneously reverted within an hour of the procedure before discharge. Discussion: We postulate the pulsed energy delivered to break apart the calcium has the capacity to cause depolarization, and therefore, affect cardiac rhythm as seen in treatment of renal stones in the past before the introduction of routine electrocardiogram (ECG) gating. In this case, the proximity of the RCA to the right atrium caused short circuiting and development of AF in a susceptible patient. Both the pacing implications and the risk of arrhythmia needs to be investigated further and the potential for ECG gating of the pulsed energy to mitigate this effect needs to be explored to enhance the safety of this technique.